2015
DOI: 10.1016/j.jpowsour.2014.10.101
|View full text |Cite
|
Sign up to set email alerts
|

Charge–discharge characteristics of natural graphite electrode in N, N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)amide containing lithium ion for lithium-ion secondary batteries

Abstract: We investigated the electrochemical characteristics of a natural graphite electrode in room-temperature ionic liquids not containing additives. N, N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)amide (DEME-TFSA) containing lithium bis(trifluoromethylsulfonyl)amide (Li-TFSA) as the electrolyte and a natural graphite electrode as the negative electrode material were employed. The charge-discharge tests showed that the discharge capacity and the charge-discharge efficiency of the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…At the initial anodic sweep, an anodic current is observed. This behavior is also observed for pyrrolidinium-based ILs (Towada et al, 2015; Horiuchi et al, 2016). In addition, the maximum current density of the anodic peak slightly shifts to a higher potential value with the increase in cycle number.…”
Section: Resultssupporting
confidence: 59%
“…At the initial anodic sweep, an anodic current is observed. This behavior is also observed for pyrrolidinium-based ILs (Towada et al, 2015; Horiuchi et al, 2016). In addition, the maximum current density of the anodic peak slightly shifts to a higher potential value with the increase in cycle number.…”
Section: Resultssupporting
confidence: 59%
“…The EW value was 5. sweep. This phenomenon is not exclusive to the methoxymethyl substituent in the pyrrolidinium cation: ILs with methoxyethyl substituted ammonium cations also exhibited continuous anodic current at the initial anodic sweep [18]. The maximum current density of the oxidation peak shifted to a higher potential value at higher cycle number.…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that ILs with ether side chains, such as the N,N-diethyl-Nmethyl-N-(2-methoxyethyl)ammonium cation ([DEME] þ ) and [Pyr 1,1O2 ] þ , exhibit high ionic mobilities and excellent charge/ discharge characteristics [4e6,10,18]. As a result of the wide EW, it would be expected that [Pyr 1,1O1 ][FSA]/LiTFSA composites would exhibit excellent charge/discharge characteristics when using cathode materials with high oxidation potentials, such as LiFePO 4 , LiCoO 2 , and LiNi 1/3 Mn 1/3 Co 1/3 .Fig.…”
mentioning
confidence: 99%
“…In particular, the charge-discharge characteristics of the graphite electrode in the bis (trifluoromethylsulfonyl) amide (TFSA)-based RTILs without organic solvent additives are poor (2,3). In contrast, we have recently found the natural graphite electrode achieved a reasonable cycle performance in N, N-diethyl-N-methyl-N- (2-methoxyethyl) ammonium (DEME)-TFSA ( Figure 1) containing lithium bis (trifluoromethylsulfonyl) amide (Li-TFSA) without organic compounds (4).…”
Section: Introductionmentioning
confidence: 99%